Effects of vitamin E and vitamin C dietary supplementation on egg production and egg quality of laying hens exposed to a chronic heat stress - Çiftçi, M; Ertas, ON; Güler, T (Ecole Nationale Veterinaire Toulouse, 2005)
In this study, the effects of vitamin E (proportional to-tocopheryl acetate) and vitamin C (L-ascorbic acid) supplementation in diets were investigated on feed consumption, egg production, egg quality in laying hens exposed to chronic heat stress. The experiment was carried out from July 15(th) to September 15(th). A total of 120 Hyline-White Leghorn hens, 150 days old, were divided into four groups of 30 birds. One group was fed with basal diet (control group) and treatment groups were fed with the basal diet supplemented with either 125 mg of proportional to-tocopheryl acetate /kg of diet (Vit E group), and 200 mg of L-ascorbic acid /kg of diet (Vit C group) or 125 mg of proportional to-tocopheryl acetate /kg of diet plus 200 mg of L-ascorbic acid of diet (Vit E + C group). Although feed intake among groups did not significantly differ, mortality has significantly decreased in supplemented birds compared to the controls (p < 0.05), particularly in the Vit E + C group. In the same way, feed efficiency and body weight gain were significantly improved in birds co-supplemented by the 2 vitamins (p < 0.05). Egg production and egg weight were also significantly increased in treated birds (p < 0.05). Slight increases of egg specific gravity and shell thickness were observed in supplemented birds, particularly in Vit E + C group, whereas percentages of egg albumen, of egg shell and haugh units were not modified. Moreover, the percentage of egg yolk was markedly enhanced in treated animals (p < 0.05): this parameter was maximal in Vit E + C group, followed by Vit E group, then Vit C group and controls. These results show that these 2 anti-oxidant compounds, vitamin E and vitamin C, have some protective actions against heat stress-induced-deleterious effects. Therefore, dietary supplementation by 125 mg vitamin E plus 200 mg vitamin C/kg of diet may increase egg production and improve egg quality in laying hens during heat stress.
Keywords: heat stress; vitamin E; vitamin C; laying hen; dietary supplementation; egg production